DIDS prevents ischemic membrane degradation in cultured hippocampal neurons by inhibiting matrix metalloproteinase release. - Matthew E Pamenter; Julie Ryu; Serena T Hua; Guy A Perkins; Vincent L Mendiola; Xiang Q Gu; Mark H Ellisman; Gabriel G Haddad (PLoS ONE, 2012)
During stroke, cells in the infarct core exhibit rapid failure of their permeability barriers, which releases ions and inflammatory molecules that are deleterious to nearby tissue (the penumbra). Plasma membrane degradation is key to penumbral spread and is mediated by matrix metalloproteinases (MMPs), which are released via vesicular exocytosis into the extracellular fluid in response to stress. DIDS (4,4'-diisothiocyanatostilbene-2,2'-disulphonic acid) preserves membrane integrity in neurons challenged with an in vitro ischemic penumbral mimic (ischemic solution: IS) and we asked whether this action was mediated via inhibition of MMP activity. In cultured murine hippocampal neurons challenged with IS, intracellular proMMP-2 and -9 expression increased 4-10 fold and extracellular latent and active MMP isoform expression increased 2-22 fold. MMP-mediated extracellular gelatinolytic activity increased ∼20-50 fold, causing detachment of 32.1±4.5% of cells from the matrix and extensive plasma membrane degradation (>60% of cells took up vital dyes and >60% of plasma membranes were fragmented or blebbed). DIDS abolished cellular detachment and membrane degradation in neurons and the pathology-induced extracellular expression of latent and active MMPs. DIDS similarly inhibited extracellular MMP expression and cellular detachment induced by the pro-apoptotic agent staurosporine or the general proteinase agonist 4-aminophenylmercuric acetate (APMA). Conversely, DIDS-treatment did not impair stress-induced intracellular proMMP production, nor the intracellular cleavage of proMMP-2 to the active form, suggesting DIDS interferes with the vesicular extrusion of MMPs rather than directly inhibiting proteinase expression or activation. In support of this hypothesis, an antagonist of the V-type vesicular ATPase also inhibited extracellular MMP expression to a similar degree as DIDS. In addition, in a proteinase-independent model of vesicular exocytosis, DIDS prevented stimulus-evoked release of von Willebrand Factor from human umbilical vein endothelial cells. We conclude that DIDS inhibits MMP exocytosis and through this mechanism preserves neuronal membrane integrity during pathological stress.